Analisa Perhitungan Daya Dukung Fondasi Minipile pada Rumah Trafo PT. Pertamina Plaju - Putra, M. Sang Gumilar Panca; Amalia, Kiki Rizky; Syahira, Nurul Aina; Praditya, Norca; Marpen, Rio (Universitas Batanghari Jambi, 2024)
Substructure is more commonly known as a foundation. Foundations come in many types, and the selection of the foundation type is based on soil conditions, technical requirements, environmental factors, and cost. One of the key factors in choosing a foundation is the soil bearing capacity in the area under consideration. Soil bearing capacity refers to the soil's ability to withstand all the loads acting on it. Before designing the foundation, it is essential to determine the soil bearing capacity. Soil bearing capacity is obtained from soil tests, such as the Cone Penetration Test (CPT) or Sounding. The method used in this study employs a quantitative approach with the analysis of secondary data. Based on the results of the soil tests using CPT, with cone resistance values ranging from 139 kg/cm2 to 198 kg/cm2 at depths between 11 meters to 16 meters, mini-pile foundations are used. The dimensions of the mini-pile plate are 10,000 mm x 3,800 mm x 500 mm, and 6 concrete piles with dimensions of 250 mm x 250 mm are used. The total number of 250 mm x 250 mm concrete piles required is 2.